Study of Plant Diversity in the Javan Rhino and Conservation Area (JRSCA), Ujung Kulon National Park - Siswoyo, Siswoyo; E.K.S. Harini Muntasib; Haryanto (Media Konservasi, 2024)
The Javan rhinoceros is an endangered animal that is protected according to the Minister of Environment and Forestry No. P.106 of 2018, included in the IUCN Redlist Data Book with the category of critically endangered or endangered animals, listed in Appendix I of CITES. In the framework of the conservation of the Javan Rhinoceros, the Javan Rhino and Conservation Area (JRSCA) is planned to be built in the Ujung Kulon national park area. In order to minimize the negative impact on plants in the area, it is necessary to identify the existence of protected and/or rare plant species, as well as the number of trees to be cut down, so this research is necessary. This study aimed to identify the diversity of plants in the JRSCA area that is not being developed and which will be developed, as well as to identify the species of rhinoceros food plants in the JRSCA area. Field data collection in the study of plant diversity in the JRSCA area used the quadratic method using grid lines and interviews. In the undeveloped JRSCA area, 241 plant species were found; the species diversity index ranged from 3.027 – 3.982 (trees), 2.460 – 3.573 (poles), 1.177 – 3.583 (saplings), and 2.421 – 3.262 (seedlings and understoreys); at various growth rates dominated by 7 species; found 3 species belonging to the VU/Vulnerable category and 1 plant species belonging to the EN/Endangered category according to IUCN; and found as many as 89 species of rhino food plants. In the area of the JRSCA that will be built, 141 plant species are found; density of 2,221 trees; a total of 2,221 trees planned to be felled with a TBC tree volume of 1,214.06 m3 and an TT volume of 2,314.08 m3; and found as many as 1 species including the category VU / Vulnerable according to IUCN.